Cognitive-Based Concept Mapping for Designing IRE Materials: Enhancing Meaningful Learning through Structured Knowledge - Budihargo, Mush'ab Umar; Musyaffa, Zaim Hilmi; Mabrury, Azzam (Multicultural Islamic Education Review, 2025)
This study investigates the effectiveness of concept maps, grounded in Cognitive Load Theory (CLT) and Dual Coding Theory (DCT), in promoting meaningful understanding within Islamic Religious Education (IRE) as an alternative to rote-based pedagogy that hinders deeper conceptual and reflective learning. Using a quasi-experimental pretest–posttest control-group design with two intact eleventh-grade classes at a public senior high school, the experimental group was taught with cognitively informed concept maps while the control group received traditional lectures; cognitive gains in conceptual understanding were measured via pretest and posttest assessments. Results show that the experimental group achieved significantly higher posttest scores and greater improvement, with concept maps reducing extraneous cognitive load, enhancing dual-channel information processing, and integrating abstract Islamic values into coherent conceptual structures; students also exhibited increased engagement, participation, and reflective thinking. Although limited to two classes and a single instructional topic—and without assessing long-term retention or affective outcomes—the findings indicate that cognitively grounded visual strategies can enhance conceptual learning and warrant consideration in IRE instructional and curricular design. The study contributes to the underexplored domain of cognitive theory–driven visual strategies in religious education by combining CLT and DCT with concept mapping to propose a novel pedagogical model that supports both cognitive efficiency and meaningful understanding in faith-based learning contexts.